The impact of movement education model intervention on basic movement skills of 4–5-year-old children - Syaputra, Muh. Ilham; Sandi, Sandi; Khaerul, Khaerul; Sakka, Aidil; Akbar, Muh. Ali; Haris, Iyan Nurdiyan; Rosti, Rosti (Jurnal Patriot, 2025)
Problem: This study was driven by the lack of diversity in physical education lessons in schools, thus limiting the optimal development of children's basic motor skills. Purpose: This study aims to determine the impact of implementing a movement-based learning model on improving basic motor skills in children aged 4-5 years at Al-Hidayah Kindergarten, Lambopini Village, Iwoimenda District, Kolaka Regency. Methods: The method used was a quasi-experimental design with a pre-test and post-test in one group, with 15 students taken from the sample. Data collection was carried out using the Basic Motor Ability Test which includes locomotor, non-locomotor, and manipulative aspects, which was carried out before and after the intervention for six sessions. Result: The results in this study, referring to the paired t-test analysis, showed a significant difference between the pre-test and post-test scores with an average increase of 16.4 points and a significance value of 0.000 (<0.05). The results indicate that a structured basic movement learning model based on active games and adapted to the child's developmental stage is effective in improving coordination, agility, muscle strength, and confidence in performing movements. Conclusion: In conclusion, basic movement learning is effective in developing basic motor skills in childhood and can be an appropriate physical education strategy for teachers in rural areas with limited resources.